Allogeneic stem cell transplant in non-Hodgkin lymphomas: Still an indication? - Dreger, Peter (Hematological oncology, 2021)
Allogeneic hematopoietic cell transplantation (alloHCT) used to play a defined role in the treatment of non-Hodgkin lymphoma (NHL). With the advent of modern targeted molecular therapies and immunotherapies, treatment standards at least for B-cell lymphoma have undergone significant changes, thereby questioning the traditional role of alloHCT in these diseases. This paper attempts to describe the current place and the perspectives of alloHCT in the rapidly evolving treatment landscape of NHL.
Gesehen am 02.07.2021